Fuzzy logic for plant-wide control of biological wastewater treatment process including greenhouse gas emissions. (June 2018) - Santín, I.; Barbu, M.; Pedret, C.; Vilanova, R.
Abstract: The application of control strategies is increasingly used in wastewater treatment plants with the aim of improving effluent quality and reducing operating costs. Due to concerns about the progressive growth of greenhouse gas emissions (GHG), these are also currently being evaluated in wastewater treatment plants. The present article proposes a fuzzy controller for plant-wide control of the biological wastewater treatment process. Its design is based on 14 inputs and 6 outputs in order to reduce GHG emissions, nutrient concentration in the effluent and operational costs. The article explains and shows the effect of each one of the inputs and outputs of the fuzzy controller, as well as the relationship between them. Benchmark Simulation Model no 2 Gas is used for testing the proposed control strategy. The results of simulation results show that the fuzzy controller is able to reduce GHG emissions while improving, at the same time, the common criteria of effluent quality and operational costs. Graphical abstract: Highlights: Fuzzy logic for plant-wide control of wastewater treatment process. Nitrous oxide reduction by manipulating dissolved oxygen of aerated reactors. Effluent quality, operational costs and other GHG emissions are also improved. Benchmark Simulation Model No 2 Gas is used for simulation.